Dari Islamisme ke “Premanisme”: PergeseranOrientasi Gerakan Kelompok Islam Radikal DiEra Desentralisasi Demokrasi - Kafid, Nur (UI Scholars Hub, 2016)
This article was wrote based on a study to describe the shifting orientation of hard-line Islamic group in the decentralization of democratic era and its influences factor: from “Islamism” to “premanism”. Islamism, which at the beginning used as the main issue, has been shifted to occupying the economic resources. Through the qualitative method, the data gathered showed that this changing orientation as the “metamorphosed” form of movement which becomes one of their survival ways. Political clientelism practiced by New Order regime has been re-emerging in the different types. Patron which at the time is fully dominated by the government leader nowadays has spread out to the various parties in the local region who have access and control to the economic resources.